The THE SUWUK TRADITION USING ACCESSORIES WITH THE RECITATION OF THE QUR'AN: Comparative Study of The Opinions of Yusuf Al-Qaraḍawī and ʿabd Al-ʿazīz Ibn ʿabd Allāh Ibn Bāz - Waliyuddin Yusuf; Imron Rosyadi; Fahruddin Ali Sabri; Satria Kamal Akhmad (Journal of Indonesian Comparative of Syari'ah Law, 2025)
the Javanese ethnic community is very familiar with and familiar with the tradition of wearing accessories accompanied by Quranic recitation. This issue has been a topic of discussion among Middle Eastern scholars. Yusuf al-Qaraḍawī and ʿAbd al-ʿAzīz ibn ʿAbd Allāh ibn Bāz have their respective opinions on this phenomenon.The author used descriptive qualitative research techniques based on a literature review. The data sources for this study consisted of primary sources, namely the book